A STUDY ON SPEAKING SKILL ACTIVITIES IN AR-ROHMAH ENGLISH COMMUNITY PROGRAM IN SMA AR-ROHMAH MALANG - Adnin Hayatinnufus (University of Muhammadiyah Malang, 2018)
Ar-rohmah English Community is an extracurricular program which provides time and creates opportunity to learn English speaking skill. The aims of this study are to describe kinds of speaking activities used in Ar-Rohmah English Community Program in SMA Ar-Rohmah Malang, to find out the problems related to teaching and learning English speaking skill activities in AEC Program and to investigate the solutions for the problems. The use of research design in this study was descriptive qualitative in which the instrument used to get the data were observation, questionnaire and interview. It was presumed as the proper design in order to attain the purpose in overcoming and solving the research problems. This study obtained the data from twenty-four students and two English teachers who were involved in the AEC Program. After analyzing the data, it is found that English teachers use seven speaking activities in Ar-Rohmah English Community Program. Those seven activities are free speaking, card game, watching movie, interview, storytelling, science writing presentation and dialogue activities. Furthermore, the problems found related to teaching and learning English speaking skill are derived from linguistic and non-linguistic factors. From linguistic factors, it is found that the students face the difficulty on mastering vocabulary, choosing appropriate grammar, lacking of pronunciation experience and not habituated with English. Moreover, from non-linguistic factor, they are reluctant to speak in English because they are inhibited, have nothing to say, have low participation and feel ease and safe using mother tongue language. Besides, the teachers face the difficulty such as get tired to handle a large class with only two teachers, confused to choose suitable activity, do not remember students’ names, hard to motivate the students to speak in English and lack of preparation time. In addition, other activity which is Pandu Hidayatullah influences the students’ passion toward AEC Program. Dealing with those problems, the teachers keep creating creative, fun and interesting activity to improve the students’ vocabulary, grammar, pronunciation and familiarized the students with English. By creating regulations, they solve the problems of students’ low motivation to use English hard to push the students using English